Cross-border provision of services: Case study in the Slovak Republic - Daniela Nováčková; Lucia Paškrtová; Jana Vnuková (Administrative Sciences, 2023)
The European Union places great emphasis on removing obstacles within its internal market, which is considered a fundamental pillar of European economic integration. By way of legal acts, the conditions for the functioning freedoms of the internal market are harmonized in all EU Member States. In our study, we focus on freedom to provide services, in order to clarify the system and conditions for providing cross-border services and to identify concrete entities providing this kind of services in Slovakia. The subject of the study is the provision of services by foreign entities in the territory of the Slovak Republic, who have already obtained authorization to perform the services on the territory of their Member State of establishment in accordance with Directive 2006/123/EC of the European Parliament and of the Council of 12 December 2006 on services in the internal market (OJ L 376, 27 December 2006, pp. 36-68). At the same time, the study also focuses on the system of taxation of cross-border services. Based on facts and data obtained from the Register of Cross-border Services, we have identified areas of providing cross-border services in Slovakia. In our study, we have applied the methods of comparative analysis, legal research, the study of literature, and the decisions of the EU Court of Justice. The study also includes clarification of the concept of cross-border provision of services.
Keywords: 350; economic integration; barriers; free movement of services; internal market; Slovak Republic